Enhancing Critical Thinking in Society 5.0: An Evaluation of High Order Thinking Skills (HOTS) in Secondary Education - Zahri, Triave Nuzila; Syukur, Yarmis; Sari, Azmatul Khairiah; Sari, Resti Elma; Cusinia, Azahra Hardi (Universitas Negeri Padang, 2023)
The learning process in the Society 5.0 era requires students to develop critical thinking skills. Higher Order Thinking Skills (HOTS) play a crucial role in shaping students into creative, analytical, and independent learners. These skills involve the ability to analyze, evaluate, and generate new ideas. However, many students struggle with HOTS-based learning patterns because they are accustomed to conventional teaching methods. Students who are unprepared for HOTS-based learning find it difficult to adapt to the demands of critical thinking, problem-solving, and analytical skills. This descriptive comparative study aims to evaluate students' learning skills based on HOTS and examine gender-based differences in these skills. The population of this study consists of 879 students from Junior High School Number 30 Padang, with a sample of 265 students selected using stratified random sampling. Data were collected through a Likert-scale questionnaire measuring students' abilities in three sub-variables: completing assignments, answering exams, and participating in learning activities. Descriptive statistical analysis shows that students' mastery of HOTS-based learning skills is 77% in completing assignments, 77% in answering exams, and 76% in participating in learning activities. The results of an independent t-test indicate that female students demonstrate better mastery of HOTS-based learning skills than male students. These findings highlight the importance of schools enhancing students' HOTS-based learning skills to improve academic outcomes and better prepare them for future challenges.